ВДОСКОНАЛЕННЯ МОНІТОРИНГУ ТЕХНІЧНОГО СТАНУ МЕХАНІЧНИХ ЕЛЕМЕНТІВ ВИСОКОВОЛЬТНИХ ВИМИКАЧІВ - Панов, А.В.; Паньків , В.І.; Сопель, М.Ф.; Танкевич, Є.М. (Інститут електродинаміки Національної академії наук України, 2018)
Based on the consideration of the structure, physical processes and functioning of the control unit and drive mechanism of the high-voltage circuit breaker, an analysis of the diagnostic indicators and indicators of monitoring and the methods of their determination from the point of view of information value, justification and efficiency of use in the circuit breaker on-line monitoring systems has been made. The method and algorithm of complex automatic determination of monitoring parameters of circuit breaker mechanical elements, including a number of new indicators which are offered in the paper, related to trip/close coils such as local extremes of currents and their corresponding time instants, active resistance, inductance and time constant of the coil current are proposed. References 13, figures 6.